Unexpected favorable outcome to etoposide and cisplatin in a small cell lung cancer transformed patient: a case report - Xie, Zhanhong (Cancer Biol Ther, 2019)
Patients with epidermal growth factor receptor (EGFR) mutant non-small cell lung cancer can benefit significantly from EGFR tyrosine-kinase inhibitors (TKIs) treatment, but almost every patient will inevitably develop resistance. The transformation to small cell lung cancer (SCLC) has been described as an EGFR-TKI resistance often associated with aggressive clinical course and poor prognosis. In this study, we report an unexpected favorable response to etoposide and cisplatin (EP) from an EGFR-mutant patient who developed SCLC transformation at disease progression after the administration of erlotinib with a progression-free survivalof 7.7 months. At disease progression (PD) after erlotinib, rebiopsy showed typical SCLC histology accompanied by positive expressions of CD56, TTF-1, CK7, and synaptophysin. Subsequently, he was switched to standard SCLC treatment regimen EP in combination with erlotinib due to the retention of EGFR 19 del and achieved PR four cycles after the treatment. His disease progressed again 7.7 months after the initiation of EP treatment, with an enlargement of both primary and metastatic lesions. Collectively, this case illustrated the transformation from adenocarcinoma to SCLC and the subsequent durable benefit from standard treatment for SCLC.